EXPLORING THE RELATION BETWEEN EDUCATIONAL BACKGROUND-JOB MISMATCH AND EMPLOYEE PERFORMANCE AT BNI REGIONAL OFFICE MANADO - Lomban, Firginia Christien; Saerang, David P. E. (Universitas Sam Ratulangi, 2016)
Employee have become the popular topics in human resources concept today. There are many factors that can influence employee performance such as motivation, job satisfication, work environment, rewards, job security and also educational background of employee. Phenomenon that exists today which is educational background-job mismatch. Educational background-job mismatch is the mismatch between the level of education ( under education, over education ) and field of study ( horizontal ) with what education background that really required. The objective of this study is to explore the relation between Educational Background-Job Mismatch and Employee Performance on Bank BNI Wilayah Manado Office. This study using qualitative research method for 13 informant that comes from different division in BNI who graduated from many different variety of educational background in terms of fields of study ( horizontal mismatch) .This study founds;factor that can influence the performance of employee in BNI is training, educational background if it is related to field of study had a negative influence to employee performance. It is caused by; BNI is one of company that give an oppurtunity to many different faculty to developed their career in their company. Many of people posses only to have a job as soon as possible without caring if that job match with their educational background and the last, there are many graduated student confronted with less work place. Keywords: employee performance, educational background-job mismatch